Սբ. Ամենափրկիչ Վանքի դպրոցը և Կոստանդ Ջուղայեցու Դասագիրք Մատյանը - Բողոզյան, Սոսե (Արմավ հրատ.)
Kostant (also Kostantin) Jughayetsi is one of the key figures of New Julfa of the 17th century, a merchant, a scientist-monk, a pedagogue anda teacher of the school of the Surb Amenaprkich monastery. He is the author of the first Armenian trade textbook “Compendium” and the founder of the trade literature genre in the Armenian literature. He has written “The Art of Arithmetic”, “The Introduction to Arithmetic” and “Compendium”, which summarize the knowledge and experience gained over the years of his trade activities. Our article is devoted to the chronicle heritage of Kostant Jughayetsi, in particular, to the works included in his textbook “Compendium”: “Instruction for Newly Learned and Young Merchants, “Question and Answer”, “Read, Baby, Learn with Love”, “Glory to You, the Heavenly Father” and “Ayb is an Example for All”.One of the ancient copies of the “Compendium”, being in the book depository of the Surb Amenaprkich Monastery of New Julfa, is the subject of our research. The “Commercial Commandment” by Kostant Jughayetsi is a whole encyclopedia of the materials necessary for the trade business, which summarizes advice and knowledge related to this area. The remaining works mainly represent the samples of the medieval instructions of the secular and spiritual content. Although these works do not represent great artistic value, they contain valuable information about the everyday lifeof that time andsupplement the picture of the literary heritage of New Julfa, being an important source of the history of the Armenian pedagogy and bibliography. Костант (также Костантин) Джугаеци — одна из ключевых фигур Новой Джульфы XVII в., купец, ученый монах, педагог, преподаватель школы монастыря Сурб Аменапркич. Он является автором первого армянского торгового учебника «Компендиум» и основоположником жанра торговой литературы в армянской литературе. Его перу принадлежат «Искусство арифметики», «Введение варифметику» торговой деятельности. Наша статья посвящена летописному наследию Костанта Джугаеци, в частности произведениям, вошедшим в его учебник «Компендиум»: «Наставление новообучающимся и молодым купцам», «Вопрос и ответ», «Читай, малыш, учись с любовью», «Слава тебе, небесный Отец» и «Айб для всех пример». Предметом нашего исследования является одна из древних копий «Компендиума», находящаяся в книгохранилище монастыря Сурб Аменапркич Новой Джульфы. «Коммерческаязаповедь» Костанта Джугаеци — это целая энциклопедия материалов, необходимых для торгового дела, в которой обобщаются советы и знания, относящиеся к этой сфере. Остальные труды в основном представляют собой образцы средневековых наставлений светского и духовного содержания. Эти произведения, хотя и не представляют большой художественной ценности, однако содержат ценные сведения о жизни и быте того времени, дополняют картину литературного наследия Новой Джульфы, являясь важным источником истории армянской педагогики и библиографии.
Keywords: Հայոց եկեղեցի